PENGGUNAAN MODEL PROBLEM SOLVING DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Zuraida Zuraida (Pedagogi: Jurnal Ilmu Pendidikan, 2014)
In the process of learning social studies teachers should provide opportunities for students to participate, collaboration, critical thinking, activities, in finding and solving problems ditemuinyai. It can be given by the teacher through various problems in IPS. It is more appropriate to find and solve problems in pemebelajaran IPS is to use the model of Problem Solving. The problem in this case is, 1) the teacher presents material exposure to verbal and IPS interview, in which teachers rarely provide opportunities for students to find and solve the problems contained in IPS.2 learning) students' mastery of subject matter IPS less condition this resulted in lower student learning outcomes. Peneitian goal is to improve the learning process of social studies and student learning outcomes. This type of research is a classroom action research, with qualitative and quantitative approaches. as much as 2 cycle consists of planning, implementation, observation and reflection.